(3cJGH JgPjH EUdGM GdefWbs - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3GHf GdScjJ , jYbhH Hf GSMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s ((3ESeGYjd Hf YHO Gddg Hf WGgQ GdbheGfi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI Ydi fHjg eMeO hBdg aEfi deG QCjJ ejd CcKQ GdfGS Edi cJGH EUdGM GdefWb dCHi jhSa jYbhH Hf ESMGb GdScjJ HGH aYd haYd HGNJdGa GdeYfi s
(3BNQgG (B:s
(3aEf EJab JcedI HYV GdCdaGX ai ehGVY efg adCfg dGjecf EaQGOg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HChdg hbajI hSeGYs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
Keywords: (3GddZIs